2010
DOI: 10.1038/labinvest.2010.79
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα expression is associated with homeostasis of the gastric epithelium and with gastric carcinogenesis

Abstract: Transcription factors from the CCAAT/enhancer-binding protein (C/EBP) family are fundamental for the control of differentiation and proliferation of many adult tissues. C/EBPa has a crucial role in inducing terminal differentiation and is an established tumor suppressor gene in several cancer models. The objective of this study was to analyze the putative role of C/EBPa in gastric carcinoma (GC). We analyzed the expression of C/EBPa in normal and neoplastic gastric tissues, and assessed the role of C/EBPa on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…C/EBPα is aberrantly silenced in pancreatic cancer cells and restored C/EBPα gene expression markedly suppressed proliferation of pancreatic cancer cells [13]. In gastric carcinoma, loss of C/EBPα is associated with the switch from cellular differentiation to cellular proliferation, presumably as a result of the activation of Ras/MAPK pathway [14]. In addition, methylation in the promoter of C/EBPα gene occurred at a rate of 24% in dedifferentiated liposarcoma (DLPS).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPα is aberrantly silenced in pancreatic cancer cells and restored C/EBPα gene expression markedly suppressed proliferation of pancreatic cancer cells [13]. In gastric carcinoma, loss of C/EBPα is associated with the switch from cellular differentiation to cellular proliferation, presumably as a result of the activation of Ras/MAPK pathway [14]. In addition, methylation in the promoter of C/EBPα gene occurred at a rate of 24% in dedifferentiated liposarcoma (DLPS).…”
Section: Discussionmentioning
confidence: 99%
“…Through C/EBPα(CCAAT/enhancer-binding protein α) signaling pathway, the expression of TFF1 is increased and GC cells have a pronounced reducing in proliferation [129]. Soutto et al [130] reported that loss of TFF1 facilitated β-catenin activation and gastric tumorigenesis through AKT/GSK3β/β-catenin signaling pathway.…”
Section: Othersmentioning
confidence: 99%
“…As a tumor suppressor, C/EBPα was found to be downregulated in several types of cancer and regulated cancer cell behaviors such as proliferation, differentiation and metabolism [12, 13]. In the lung, C/EBPα is highly expressed in alveolar type II cells, Clara cells, and alveolar macro-phages [14, 15].…”
Section: Introductionmentioning
confidence: 99%